18 USE OF ANTI-INFLAMMATORY MEDICATIONS IN PATIENTS WITH CHRONIC LUNG DISEASE OF INFANCY. (1st January 2006) - Nenninger, T.; Chin, T.; Akanli, L.; Fanous, Y.
Abstract : Treatment of children with a history of bronchopulmonary dysplasia (BPD) often includes the use of anti-inflammatory medications. However, long-term studies examining their long-term use are few. We conducted a retrospective study to determine the effects of an aerosolized corticosteroid (Pulmicort®) and the leukotriene antagonist montelukast (Singular®) in oxygen-dependent infants followed in the BPD Center at Loma Linda University Children's Hospital. Group A includes 20 infants treated with Pulmicort. Group B includes 13 treated with both Pulmicort and Singular. Group C includes 7 who were not treated with either Singular or Pulmicort. Within these three groups, the following were noted and compared using ANOVA tests: duration of oxygen therapy in days, number of inpatient visits to a hospital, number of ER visits, change in weight in kilograms, and change in height in centimeters. No significant differences were noted in these variables among the three test groups. However, differences in more subjective perimeters such as overall quality of life or control of allergies were not taken into account in this study.